Respuesta :

Answer:

The expression  (2 x 3) + 13  - 1   on simplifying gives 18.

Step-by-step explanation:

Here, the outcome of the expression is 18.

Using at least three operations.

Here, we use three operations Addition = '+' , Subtraction =  '-' and

Multiplication  = 'X'

Take the number 2 and multiply it with other number 3.

We get 2 x 3  = 6

Take the product, add it with another number  13

So, 6+ 13=  19

Take the resultant and subtract 1 from it.

We get 19 - 1 = 18

⇒The combined expression is (2 x 3) + 13  - 1  = 18

The above expression on simplifying gives 18.

ACCESS MORE